O trudnej sztuce czytania Miłosza (ze zrozumieniem) słów kilka - Lewandowski, Wacław (Postscriptum Polonistyczne, 2020)
The article aims to initiate a discussion on reading and interpreting poetic works by Czesław Miłosz. Discussing an example of City Without a Name the author of the article presents the deficiences of so far dominant interpretations. He also presents the specific reception of poet’s works among literary critics.